Bopopia, a new monotypic genus of Gesneriaceae (Gesnerioideae, Coronanthereae) from New Caledonia - Morel, Jérémie; Duminil, Jérôme; Munzinger, Jérôme (European Journal of Taxonomy, 2021)
A new genus of Gesneriaceae, Bopopia Munzinger & J.R.Morel gen. nov., is described from New Caledonia. The genus is based on B. parviflora Munzinger & J.R.Morel gen. et sp. nov., a new species collected during an expedition on Mt Katalupaik, in the North Province of New Caledonia’s main island. Originally considered as a species of Coronanthera, our phylogenetic analysis – including 19 species within Coronanthereae and two individuals of B. parviflora gen. et sp. nov., and using three molecular markers (nuclear rDNA ITS, and chloroplast regions trnL-trnF and trnE-trnT) – showed that the new species is not close to Coronanthera in subtribe Coronantherinae, but belongs to subtribe Negriinae where it is sister to Depanthus. From that genus Bopopia gen. nov. differs in floral symmetry (zygomorphic vs actinomorphic) and the number of stamens (4 vs 5). From the other genera of Negriinae the new genus differs in the white corolla and its indeterminate thyrse with 3 to 5 levels of branching. The morphological circumscription of the subtribe Negriinae is amended to include Bopopia gen. nov. Two keys are provided, one to the subtribes in the tribe Coronanthereae, and one to the genera in subtribe Negriinae. Following the IUCN Red List categories and criteria, the conservation status of B. parviflora gen. et sp. nov. is provisionally assessed as Endangered (EN).